What do we know about Korean Outward Foreign Direct Investment? Applying Spatial Models - Liu, Yi-Cheng; Yang, Wen; Wen-Jen, Hsu (Asian Journal of Economic Modelling, 2020)
This paper aims to prove that Korean outward foreign direct investment (OFDI) can be more comprehensively examined and major locational determinants are accurately identified when spatial dependence and heteroscedasticity effects are taken into consideration. This paper is the first one to adopt Spatial Durbin Model as the most appropriate approach in investigating Korean OFDI after a series of statistical tests. Our findings are different from the results of earlier studies without the spatial effects perspective. The empirical evidence signifies that the GDP per capita of Korean main trade-partner countries was the major Korean OFDI determinants. Korean OFDI favored economies with a higher degree of trade openness. Korean OFDI also took advantage of the economic integration. Meanwhile, it greatly underweighted its investment in most South Asian countries, South American, and African continent while Korean OFDI has outstandingly expanded into North America, the European Union, East Asian countries and mainland China markets. These provide important implications to the management of the corporate strategy and government policies on OFDI.